The Use of OJT (on the Job Training) as English Tour Guide in Teaching Speaking Ability in Pang Pang Tanjung Pasir - Ahmad Faruk; Kunna Nandya Ayu Farida Nandya (Darussalam English Journal (DEJ), 2022)
The purpose of this study is to describe how the use of OJT (On Job Training) as an English tour guide to improving students' speaking skills in Pang Pang Tanjung Pasir tour at Usaha Jasa Wisata of LKP ALOHA Tegaldlimo. It is hoped that OJT (On the Job Training) as an English tour guide can improve students' English speaking skills. The method used in this research is descriptive qualitative research. Instruments for collecting data are observation, interviews, and documentation. The researcher analyzed the data using descriptive qualitative research. From the results of the study, researchers found answers to research problems, including 1) OJT (On the Job Training) as a tour becomes an effective speaking teaching to be applied by LKP Aloha EDU teachers in the tourism service business class. Moreover, the ojt method could enhance speaking skills. 2) With OJT (On The Job Training) as a tour guide, students can practice working as a tour guide and find out the challenge that exists in the field of work.3) The problems faced during the OJT (On Job Training) process as a tour guide are students who sometimes have difficulty understanding the accent of conversations with native tourists, pronunciation, content, and vocabulary, which caused a lack of confidence in students.